2015
DOI: 10.1007/s00167-015-3857-4
|View full text |Cite
|
Sign up to set email alerts
|

How sensitive and specific is 1.5 Tesla MRI for diagnosing injuries in patients with knee dislocation?

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…The value of MRI for diagnosing isolated ligament injuries has been widely demonstrated, however, in terms of multi-ligament injuries, the accuracy of MRI is controversial. Derby et al [ 8 ] found that MRI was sensitive in detecting injuries of cruciate and collateral ligaments, but not reliable in diagnosing injury to the meniscus or posterolateral corner (PLC). Twaddle et al [ 9 ] demonstrated that MRI is not reliable for revealing injuries of the lateral collateral ligament (LCL) and PLC.…”
Section: Introductionmentioning
confidence: 99%
“…The value of MRI for diagnosing isolated ligament injuries has been widely demonstrated, however, in terms of multi-ligament injuries, the accuracy of MRI is controversial. Derby et al [ 8 ] found that MRI was sensitive in detecting injuries of cruciate and collateral ligaments, but not reliable in diagnosing injury to the meniscus or posterolateral corner (PLC). Twaddle et al [ 9 ] demonstrated that MRI is not reliable for revealing injuries of the lateral collateral ligament (LCL) and PLC.…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of studies comparing MRI findings with arthroscopic examination for other big joints. 17,[30][31][32][33] The reported sensitivity and specificity of MRI for assessing ligament injuries around the major joints were 9 to 100% and 38 to 100%, respectively. Therefore, in addition to MRI findings, the history of the patient, and physical and radiological findings, arthroscopic examination is important for assessing the extent of the injury and optimizing the surgical treatment of ligament injuries around the thumb MCPJ.…”
Section: Discussionmentioning
confidence: 99%
“…36 Finally, this study included acute (<4 weeks after injury) and chronic (>4 weeks after injury) injuries, which may not reflect the true accuracy of the MRI. 30…”
Section: Discussionmentioning
confidence: 99%
“…However, there were several limitations in this analysis 1 : differences in the inclusion criteria and exclusion criteria for patients 2 ; different patients with previous disease and treatments were unavailable 3 ; all the included studies were from English articles, which may be the source of bias 4 ; the fluency of technicians between different studies varied 5 ; difference in the MRI FS 6 ; pooled data were used for analysis; and individual patients' data was unavailable, which limited us to perform more comprehensive analysis. However, there was no significant publication bias of the included studies.…”
Section: Discussionmentioning
confidence: 99%